PENDEKATAN KONSELING INDIGENOUS: KEKUATAN NILAI PESANTREN DALAM MEMBIMBING SANTRI - Nursilah, Bayi; Trisna Putri, Syifa Nabila; Mabsuthoh, Siti; Agus Sukirno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the indigenous approach in pesantren-based guidance as an epistemological alternative to the dominance of Western counseling models. The indigenous approach positions the local wisdom of communities as the epistemological foundation of education and guidance, rather than merely as a curricular supplement. Pesantren, as the oldest Islamic educational institution in the Indonesian archipelago, has organically developed a guidance system rooted in the values of sincerity (ikhlas), simplicity (kesederhanaan), independence (kemandirian), Islamic brotherhood (ukhuwah Islamiyah), and freedom of thought within the framework of adab. The role of kiai and ustaz as indigenous counselors is manifested through the integration of fiqh values, Sufism (tasawuf), and local wisdom in daily guidance practice. Distinctive pesantren guidance practices such as halaqah, muhasabah, dhikr, mujadalah, and riyadhah demonstrate strong conceptual correspondence with modern therapeutic techniques including group therapy, cognitive behavioral therapy (CBT), mindfulness-based stress reduction (MBSR), and motivational interviewing. This study concludes that the pesantren-based guidance model is not merely a traditional practice in need of modernization, but rather a complete, humanistic, and contextual counseling system worthy of scientific formulation as a contribution to the development of guidance and counseling theory in Indonesia.